Company and its social responsibility for sustainable economic development - Martínez Prats, Germán (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The company is an organization where an economic activity of production or service is developed, to satisfy the needs of society. Representing an important part for economic development, thanks to the impact it causes by attracting new companies and consumers to support their operations, to obtain sustainable growth according to their economic activity. The objective of this document is to describe the importance that companies have in their application of social responsibility among the actors of society, the environment and business.